Serum potassium level used as trigger doubled the detection of adverse drug events when compared with calcium polystyrene sulfonate trigger: A cross-sectional study - Mastroianni, Patricia de Carvalho [UNESP]; Vieira Borges, Marina [UNESP]; Forgerini, Marcela [UNESP]; de Nadai, Tales Rubens; Varallo, Fabiana Rossi (Editora Cubo, 2021)
Background: Prescription of calcium polystyrene sulfonate (CPS) has been considered a trigger with good performance to detect hyperkalemia related to adverse drug events (ADE). However, CPS prescription may underestimate the rate of ADE. Objective: To compare the performance of the serum potassium level (SPL) >5.0mEq/L and CPS triggers in detecting hyperkalemia related to ADE. Design and setting: A six-month cross-sectional study was conducted in a Brazilian medium-complexity public hospital. Methods: SPL Tests with results >5.0mEq/L and the prescriptions of CPS of all patients hospitalized in the internal medicine and infectious diseases wards were used as trigger tools to detect potential ADE. Primary outcome: patients with hyperkalemia related to ADE. Secondary outcomes: effectiveness of treatments and ADE. Variables analyzed were SPL tests, CPS prescriptions, treatments of hyperkalemia and comorbidities. Positive predictive values (PPV) of CPS and SPL triggers were calculated and compared. Results: In total 2,466 SPL tests were assessed, of which 513 were triggered (>5.0mEq/L). The tests triggered 198 patients with hyperkalemia, of whom 121 had hyperkalemia related to ADE (PPV=0.61). In total, 101 CPS prescriptions triggered tests in 35 patients with hyperkalemia, among whom 21 cases were related to ADE (PPV=0.60). SPL detected 204 ADE (PPV=0.40), while CPS prescription detected 22 (PPV=0.21). Seven pharmacological and four non-pharmacological treatments were identified. CPS showed the lowest effectiveness (PPV=0.71). Conclusion: SPL>5.0mEq/L increased the detection of ADE by 9.3-fold, the number of patients tracked with hyperkalemia related to ADE by 5.8-fold, and doubled the performance in detection of ADE in comparison with the prescription of the CPS trigger.
Keywords: Drug Monitoring; Drug-Related Side Effects and Adverse Reactions; Hyperkalemia; Outcome Assessment; Safety Management